Drosophila: a model for understanding obesity and diabetic complications - Teleman, Aurelio A.; Göbel-Ratzenböck, Ingrid; Oldham, Sean (Experimental and clinical endocrinology & diabetes, 2012)
The molecular mechanisms underlying development of obesity and diabetic complications are not well understood. Drosophila has become a popular model organism for studying a variety of human diseases. We discuss here emerging Drosophila models of obesity and diabetic complications.